A thermochemical study of thiol collector surface reactions on galena and chalcopyrite. (July 2015) - McFadzean, B.; Moller, K.P.; O'Connor, C.T.
Highlights: Surface reactions of thiol collectors with galena and chalcopyrite were studied. Heat evolved in real time was tracked. Reaction mechanisms were different for different collectors with the same mineral. Reaction mechanisms were different for different minerals with the same collector. Collector interactions were weaker when using mineral mixtures due to passivation. Abstract: The mechanism whereby thiol collectors adsorb onto a mineral surface has been widely studied. Most of these studies examine the mineral surface at equilibrium state and, often, well above monolayer coverage. However, the formation of species at the mineral surface is a complex process that is both kinetically and thermodynamically controlled. In a typical industrial application, the dosage of collector will be around monolayer level. This study uses isothermal titration microcalorimetry to measure the heat evolved during the reaction of sodium ethyl xanthate (SEX) and sodium isobutyl dithiocarbamate (SIBDTC) and their mixtures with galena and chalcopyrite. The sensitivity of the instrument allows heats of reaction of sub-monolayer quantities of thiol collector to be measured. The study found that the nature of the reaction between a collector and a mineral surface was dependent on the type of mineral and the type of collector. Proposals are made for the reactions based on previously reported results and the evidence from this investigation. It was found that when collectors reacted with mixtures of galena and chalcopyrite, the magnitude of the reaction was lower compared to that measured for the pure minerals alone. This may be due to galvanic interactions between the minerals, resulting in a passivating effect on one or both of the minerals.